The Ins and Outs of Autophagy and Metabolism in Hematopoietic and Leukemic Stem Cells: Food for Thought - Ianniciello, Angela; Rattigan, Kevin M.; Helgason, G. Vignir (Frontiers in Cell and Developmental Biology, 2018)
Discovered over fifty years ago, autophagy is a double-edged blade. On one hand, it regulates cellular energy sources by “cannibalisation” of its own cellular components, feeding on proteins and other unused cytoplasmic factors. On the other, it is a recycling process that removes dangerous waste from the cytoplasm keeping the cell clean and healthy. Failure of the autophagic machinery is translated in dysfunction of the immune response, in ageing, and in the progression of pathologies such as Parkinson disease, diabetes, and cancer. Further investigation identified autophagy with a protective role in specific types of cancer, whereas in other cases it can promote tumorigenesis. Evidence shows that treatment with chemotherapeutics can upregulate autophagy in order to maintain a stable intracellular environment promoting drug resistance and cell survival. Leukaemia, a blood derived cancer, represents one of the malignancies in which autophagy is responsible for drug treatment failure. Inhibition of autophagy is becoming a strategic target for leukaemic stem cell eradication. Interestingly, the latest findings demonstrate that leukaemic stem cells show higher levels of mitochondrial metabolism compared to normal stem cells. With this review, we aim to explore the links between autophagy and metabolism in the haematopoietic system, with special focus on primitive leukaemic stem cells.